Taksu and Pangus As An Aesthetic Concept Entity of Bali Dance (A Case Study of Topeng Tua Dance) - Mariasa, I Nengah (Harmonia: Journal of Arts Research and Education, 2015)
There are two types of topeng drama performance (topeng is Bahasa Indonesia for mask) in Bali, Topeng Pajegan and Topeng Panca. Topeng Pajegan is a masked drama performance that is danced by a dancer by playing various tapel, while Topeng Panca is danced by five dancers. Generally, there are three or four stages on topeng performance, i.e. panglembar, petangkilan, bebondresan, and/or pesiat. On panglembar stage, there is one dance represented the character of old people. The dance is then known as Topeng Tua (Old Mask). The costume, tapel, as well as hair worn by the dancer have been considered as one of the precious or noble artworks. The question comes up here, is the aesthetics of topeng only depended on its high aesthetic value costume and tapel? Topeng Tua performance technique is considerably not easy to be done by a beginner dancer. On the other words, it implicitly tells that the aesthetics of the dance depends closely to the dancersâ techniques. A good Topeng Tua dancer will be able to dance by using the technique of ngigelang topeng. Furthermore, the beauty of Topeng Tua does not only lay on its splendor artworks on the costume, tapel, and hair colour, but more to the ability of the dancersâ movement technique that successfully shows the beauty of taksu and pangus.